Participatory Budgeting Di Desa Lamanda Kecamatan Bontotiro Kabupaten Bulukumba - Satriani, Indra; Setiawati, Budi; Muhiddin, Amir (Universitas Muhammadiyah Makassar, 2022)
This study purposed to describe the Participatory Budgeting Process in Planning and Budgeting the Village Revenue and Expenditure Budget in Lamanda Village, as well as supporting and inhibiting factors. The research method used descriptive research with a qualitative approach. Data collection techniques were interviews, documentation, and observation. The analysis was carried out through analytical methods. The results showed that Lamanda Village had implemented Participatory Budgeting in Planning and Budgeting the Village Revenue and Expenditure Budget. The Participatory Budgeting process in Lamanda Village was carried out in stages through the hamlet deliberative forum stage, the Village Deliberation, and the village development planning deliberation forum stage. Participatory Budgeting which was carried out in Lamanda village also received supporting factors, namely the community's initiative to attend the deliberation forum, the establishment of good relations with stakeholders. Participatory Budgeting which was carried out in Lamanda Village also encountered obstacles in the form of the community's mindset about development and only focusing on physical development, and the village website had not been utilized optimally.Keywords: Participatory Budgeting, preparation of the Village RPJM